Determining the Priorities of Macroprudential Indicators in Indonesia - Parizi, Ahmat; Anas (Islamic Economics Methodology, 2025)
Financial system stability is the main prerequisite for the sustainability of a country's economic growth. In this context, macroprudential policy plays an important role in mitigating systemic risks originating from the financial and real sectors. However, the effectiveness of macroprudential policies is largely determined by the accuracy of the indicators used as early warning indicators. This study aims to determine the priority macroprudential indicators that are most relevant to Indonesia based on the assessment of experts. The method used is the Delphi method involving nine experts who have competence in the field of macroeconomics and financial stability. The analysis was carried out using statistical measures in the form of mean values, standard deviation, and interquartile range (IR) to measure the consensus level. The results showed that of the 20 macroprudential indicators analyzed, there were 13 indicators that reached consensus (convergent) and 7 indicators that did not reach consensus (divergent). The indicators with the highest priorities are the current account deficit, the adequacy of foreign exchange reserves, and the employment rate. These findings underscore the importance of external sector and labor market indicators in the macroprudential policy framework in Indonesia.